The Right Thing at the Right Time: Why Ostensive Naming Facilitates Word Learning - Axelsson, Emma L.; Churchley, Kirsten; Horst, Jessica S. (Frontiers in Psychology, 2012)
The current study examines how focusing children’s attention immediately after fast mapping improves their ability to retain novel names. Previous research suggests that young children can only retain novel names presented via referent selection if ostensive naming is provided and that such explicit naming works by increasing children’s attention to the target and decreasing their attention to the competitor objects (Horst and Samuelson, 2008). This explanation of the function of ostensive naming after referent selection trials was tested by drawing 24-month-old children’s attention to the target either by illuminating the target, covering the competitors, or both. A control group was given a social pragmatic cue (pointing). Children given social pragmatic cue support did not demonstrate retention. However, children demonstrated retention if the target object was illuminated, and also when it was illuminated and the competitors simultaneously dampened. This suggests that drawing children’s attention to the target object in a manner that helps focus children’s attention is critical for word learning via referent selection. Directing attention away from competitors while also directing attention toward a target also aids in the retention of novel words.